MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TENTANG SUMBER DAYA ALAM SERTA PEMANFAATANNYA UNTUK KEGIATAN EKONOMI MELALUI METODE PICTURE AND PICTURE DENGAN MELIHAT GAMBAR SDA SISWA KELAS IV SD ISLAM NU PUNGKURAN SEMARANG TAHUN 2017/2018 - Mohamad Yusuf; Abdul Karim (Universitas Muhammadiyah Semarang, 2017)
Natural resources as well as its utilization for economic activity, is the subject matter of IPS lesson in class IV semester I. As a teacher in SD Islam NU Pungkuran Semarang 2015/2016 lesson year Ihave a learning obstacle even though I have tried as much as possible the results have not been maximized. From formative tests, students who score less KKM. Only 4 out of 15 students meet the KKM and others have not been completed. Based on observations, because teachers have notused the right method. Teachers have not involved students in learning so that when given formative tests the results are less satisfactory. From the above problems, then the purpose of research to be achieved is how to improve understanding of the subject matter in learning IPS.After the improvement of learning cycle I and cycle II obtained increased value of repetition; In the first cycle of formative test results that get less value than KKM, there are 7 students who have not completed and have completed 8 students. While in cycle II obtained satisfactory results, allstudents complete from KKM. From the results of research improvements can be concluded learning achievement of students increased, proved because the level of mastery of a minimal classically very significant, this is because the use of picture and picture method by looking at theimage of natural resources.Keywords: IPS, SDA images, and learning outcomes